Two new species of the genus Ennearthron Mellié, 1847 (Coleoptera: Ciidae) from Yunnan Province, China - Li, Nan; Mo, Da-Rui; Mao, Ben-Yong; Xu, Ji-Shan (Zootaxa, 2024)
Ennearthron acuticornum sp. nov. and Ennearthron jizushanense sp. nov. are described and illustrated from Yunnan Province, China. The two new species have a pair of long horns on the anterior edge of the pronotum (the former with pronotal horns slender and acute, the latter develops thick and slightly shorter pronotal horns than the former) and with relatively large body size in the current known species of the genus Ennearthron Mellié.